2015
DOI: 10.1002/pmic.201400604
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the biology of alpha herpesviruses with MS‐based proteomics

Abstract: Viruses are intracellular parasites that can only replicate and spread in cells of susceptible hosts. Alpha herpesviruses (α-HVs) contain double stranded DNA genomes of at least 120 kb, encoding for 70 or more genes. The viral genome is contained in an icosahedral capsid that is surrounded by a proteinaceous tegument layer and a lipid envelope. Infection starts in epithelial cells and spreads to the peripheral nervous system (PNS). In the natural host, α-HVs establish a chronic latent infection that can be rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 113 publications
0
28
0
Order By: Relevance
“…Previously, AE-MS has successfully identified host factor interactions with viral non-structural proteins of virus families ranging from flaviviruses to herpesviruses (reviewed in Refs. [133,[147][148][149]). The application to virus receptor discovery is now in reach (Fig.…”
Section: Shotgun Proteomicsmentioning
confidence: 99%
“…Previously, AE-MS has successfully identified host factor interactions with viral non-structural proteins of virus families ranging from flaviviruses to herpesviruses (reviewed in Refs. [133,[147][148][149]). The application to virus receptor discovery is now in reach (Fig.…”
Section: Shotgun Proteomicsmentioning
confidence: 99%
“…Among these were the heat shock proteins hsp 90-beta (hsp90ab1), 90 kDa beta member 1(hsp90b1), 70 kDa protein 5(hspa5) and 105 kDa (hsph1). Similarly, hsp27 was also significant altered at 4 h of PRV infction in Madin-Darby bovine kidney cells using SILAC mass spectrometry methods, since only a small number of host cell proteins changed during early stages of PRV infection, other stress-related proteins did not show significant variations 7,8 . Heat-shock proteins can facilitate protein folding, heat-shock response activation might be a virus-specific function ensuring proper protein synthesis and; therefore, ER stress proteins may also be important for virus replication 37,39,40 .…”
Section: Discussionmentioning
confidence: 96%
“…The pathogenesis of PRV infection and the interactions between PRV and porcine cells are not fully understood at present [7][8][9] . Proteomic approaches provide effective tools for facilitating a comprehensive characterization of virus-host interactions, for example, two-dimensional gel electrophoresis (2DE) and matrix-assisted laser desorption ionization-time-of-flight mass spectrometry (MALDI-TOF/MS) approaches have been used to provide the proteomic expression profiles of host cells in response to viral infections, including classical swine fever virus 10 , severe acute respiratory syndrome 11 , H1N1 influenza virus 12 and spleen and kidney necrosis virus 13 .…”
mentioning
confidence: 99%
“…; Engel et al . ). However, no such studies have been reported for OsHV‐1, which is a clear gap that needs to be addressed in future investigations.…”
Section: Applications Of Proteomics In C Gigas Mortality Eventsmentioning
confidence: 97%